Dark shadow of the long white cloud: Neighborhood safety is associated with self-rated health and cortisol during pregnancy in Auckland, Aotearoa/New Zealand - Zaneta M. Thayer (Elsevier, 2017)
Auckland, Aotearoa/New Zealand is a culturally and ethnically diverse city. Despite popular global conceptions regarding its utopian nature, the lived experience for many individuals in Auckland attests to the substantial social, economic, and health inequalities that exist there. In particular, rapidly rising home prices constrain housing decisions and force individuals to live in less desirable neighborhoods, with potential impacts on individual health. One of the pathways through which adverse neighborhood conditions could impact health is through alterations in the functioning of the hypothalamic pituitary adrenal (HPA)-axis, which regulates the physiological stress response. This paper evaluates the relationship between perceived neighborhood safety, self-rated health, and cortisol, an end product of HPA-axis activation, among women in late pregnancy. Pregnant women living in neighborhoods where they were concerned about safety of their property had poorer self-rated health and elevated morning cortisol, even after adjusting for maternal age, material deprivation, and ethnicity. However, fear of personal safety was unrelated to self-rated health and cortisol. These results suggest that maternal health in pregnancy is sensitive to perceptions regarding neighborhood safety. Such findings are important since higher cortisol levels in pregnancy could not only influence maternal health, but also the health and development of women's children.